Knowing the Score - Bilson, Malcom; Booth, Daniel (Cornell University Press, 2005)
In this provocative video presentation, distinguished pianist Malcolm Bilson poses the question, Do we really know how to read the musical notation of the 18th- and 19th-century masters, and how can a better informed reading lead to more expressive, even passionate performance?Bilson, known worldwide for his ground-breaking recordings, has been lecturing and teaching at conservatories and music schools all over the world for the past 30 years. In recent years he has become increasingly convinced that the highly informative notation of earlier times is no longer properly understood, and that while many musicians study from the best available sources (so-called urtext editions) their interpretation of those sources may be erroneous, at times very much so.The result, believes Bilson, is a restricted understanding of the expressive message transmitted by the notation, and leads to far less flexible performances than would be engendered by a better understanding of those sources.The main body of the DVD presents Bilson in a 90-minute lecture before a live audience examining aspects of notation of Mozart, Beethoven, Chopin, Prokofiev, Schubert, and Bartók, showing clearly that there is far more expressive information in these scores than is usually presumed.During this talk, punctuated by excerpts of Bilson performing alternately on a five-octave 18th-century Viennese piano and a modern Steinway, he challenges widely accepted notions of articulation, tempo, and pedalling.The DVD also features a 45-minute interview with British pianist David Owen Norris in Bilsons music room. The two pianists demonstrate and discuss several early pianos and explore such diverse topics as the differences between English and Viennese pianos around 1800 and fingerings and bowings in urtext editions.In addition, the DVD includes a bibliography, a discography, and two stellar performances by Bilson:Schuberts Moments Musicaux nos. 2 and 3, performed on an 1830 André Stein piano in the Brahms-Saal of the Musikverein in Vienna; andHaydns Fantasia in C, on a ca. 1795 Anton Walter replica in the Music Room of the Esterháza Castle in Fertöd, Hungary.Knowing the Score is presented with French, German, and English subtitles. It features a widescreen 16:9 transfer and region-free encoding and is recorded in Dolby Digital Stereo.
Keywords: Historically informed performance